Analisis Laba Kotor Dan Piutang Usaha Terhadap Laporan Arus Kas PT Caturkarda Depo Bangunan Tbk Periode 2018- 2022 - Sholikhah, Septiana Mar'atus; Gumanti, Miswan; Dede, Dede (Jurnal Manajemen DIVERSIFIKASI, 2023)
The purpose of this study is to ascertain how trade debt and gross profit impact forecastingof future cash flows. Companies listed on the Indonesia Stock Exchange (BEI) between 2018and 2022 served as the sample for this study. Purposive sampling is the method utilized toacquire data, and financial reports are used as secondary data. With the use of the SPSS 26computer program, multiple linear regression was employed for the data analysis in thisstudy. The findings of this study indicate that gross profit and business loans have goodcapacities in predicting cash flows in the future based on the partial test conducted in thatregard. Additionally, it is advised that PT Caturkarda Depo Bangunan Tbk be capable ofmanaging gross profits and distribute them in a way that won't jeopardize the company'sability to sustain itself.